FGF1-mediated cardiomyocyte cell cycle reentry depends on the interaction of FGFR-1 and Fn14 - Novoyatleva, Tatyana; Sajjad, Amna; Pogoryelov, Denys; Patra, Chinmoy; Schermuly, Ralph T.; Engel, Felix (The FASEB Journal, 2014)
Fibroblast growth factors (FGFs) signal through FGF receptors (FGFRs) mediating a broad range of cellular functions during embryonic development, as well as disease and regeneration during adulthood. Thus, it is important to understand the underlying molecular mechanisms that modulate this system. Here, we show that FGFR-1 can interact with the TNF receptor superfamily member fibroblast growth factor-inducible molecule 14 (Fn14) resulting in cardiomyocyte cell cycle reentry. FGF1-induced cell cycle reentry in neonatal cardiomyocytes could be blocked by Fn14 inhibition, while TWEAK-induced cell cycle activation was inhibited by blocking FGFR-1 signaling. In addition, costimulation experiments revealed a synergistic effect of FGF1 and TWEAK in regard to cardiomyocyte cell cycle induction via PI3K/Akt signaling. Overexpression of Fn14 with either FGFR-1 long [FGFR-1(L)] or FGFR-1 short [FGFR-1(S)] isoforms resulted after FGF1/TWEAK stimulation in cell cycle reentry of >40% adult cardiomyocytes. Finally, coimmunoprecipitation and proximity ligation assays indicated that endogenous FGFR-1 and Fn14 interact with each other in cardiomyocytes. This interaction was strongly enhanced in the presence of their corresponding ligands, FGF1 and TWEAK. Taken together, our data suggest that FGFR-1/Fn14 interaction may represent a novel endogenous mechanism to modulate the action of these receptors and their ligands and to control cardiomyocyte cell cycle reentry.
EVALuna2:25462